2019
DOI: 10.3390/nano9030357
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Electronic Properties of TiO2 Nanoclusters and Dye–Nanocluster Systems Appropriate to Model Hybrid Photovoltaic or Photocatalytic Applications

Abstract: We report the results of a computational study of TiO2 nanoclusters of various sizes as well as of complex systems with various molecules adsorbed onto the clusters to set the ground for the modeling of charge transfer processes in hybrid organic–inorganic photovoltaics or photocatalytic degradation of pollutants. Despite the large number of existing computational studies of TiO2 clusters and in spite of the higher computing power of the typical available hardware, allowing for calculations of larger systems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 88 publications
(182 reference statements)
1
32
0
Order By: Relevance
“…In a previous study, following the work of Persson et al [52] and De Angelis et al [53] we showed that (TiO 2 ) n clusters with n less than 24 cannot properly describe the complex dye-oxide systems [54]. It was concluded that the n = 24 cluster was the smallest one that can be used well for qualitative calculations, particularly when the adsorbed molecule is rigid, as it is the case here [54,55].…”
Section: Computational Detailsmentioning
confidence: 85%
See 1 more Smart Citation
“…In a previous study, following the work of Persson et al [52] and De Angelis et al [53] we showed that (TiO 2 ) n clusters with n less than 24 cannot properly describe the complex dye-oxide systems [54]. It was concluded that the n = 24 cluster was the smallest one that can be used well for qualitative calculations, particularly when the adsorbed molecule is rigid, as it is the case here [54,55].…”
Section: Computational Detailsmentioning
confidence: 85%
“…The model clusters used has a slight deviation from the TiO 2 stoichiometry which circumvents the problem of the surface states in the gap. We introduced H atoms or -OH groups to terminate the peripheral dangling bonds, resulting in the Ti 24 O 50 H 4 , and we showed that the presence of the four H atoms does not affect the nature of the electronic spectrum [54,55].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Several methods have been used for PVK degradation. For example, penicillin V can be degraded under visible light when TiO 2 is used as a photocatalyst (21). It has also been reported that simulated sunlight is able to degrade PVK (22).…”
Section: Discussionmentioning
confidence: 99%
“…The 16S rRNA gene sequences were compared with other 16S rRNA gene sequences available in GenBank by using the Basic Local Alignment Search Tool (BLASTN) program and BLASTn database and aligned with similar sequences by using multiple sequence alignment software (21). A phylogenetic tree was constructed by applying the neighbor-joining method using the MEGA 7.0 program based on Kimura-2 parameters with 1,000 replicates of bootstrap values.…”
Section: Methodsmentioning
confidence: 99%
“…Relatively few studies so far have faced the theoretical modeling of the structural and electronic features of the dye-semiconductor interface and its effect on photocatalytic activity. A dedicated DFT investigation considered TiO 2 nanoclusters with different adsorbed dyes: a small rigid molecule based on coumarin, a larger rigid oligomethine cyanine dye with indole groups, and the penicillin V antibiotic, with a flexible backbone [79].…”
Section: Organic Dye-sensitized Tiomentioning
confidence: 99%